The Author Defending Women’s Rights: Widad Sakakini - İlknur Emekli (Şarkiyat Mecmuası)
Widad Sakakini was an important writer in contemporary Lebanese literature and made significant contributions to Lebanese literature not only with her stories but also with her novels and critical articles. Sakakini was first active in the field of writing and publishing through newspapers and is considered one of the pioneers in the field of Lebanese feminist novels. In 1934, she married the poet and doctor Zaki Mahasin and stayed in Cairo for 11 years due to her husband’s duty. During her stay in Cairo, she completed her master’s and doctoral studies and had the opportunity to meet with well-known writers of Egypt. Upon her return to Lebanon, Sakakini was then able to blend the knowledge and experiences she had gained in Egypt with her experiences in Lebanon. Widad Sakakini’s works range from stories, novels, and articles to literary, critical, and historical research. However, the most important point that draws attention is Sakakini’s interest in women’s literature and history. This study provides information about the life, literary personality, and works of Widad Sakakini as one of the pioneering female writers and critics in contemporary Lebanese literature. The impact of Widad Sakakini’s literary talent as a creative writer is evident not only in her stories and novels but also in the numerous strong critical articles she published in newspapers. Lastly, this study emphasizes its points through authors who greatly admire Widad Sakakini by regarding her literary personality and her ability to address women’s issues.